Research of wheelset active steering device for bogie with rocker type journal box positioning - LIU Huibin; NI Wenbo; MA Shaoming (机车电传动)
In the traditional design process of bogies, engineers always had to balance the conflict between the operational stability and curve negotiation performance for railway trains, which can be effectively solved by applying the wheelset active steering technology. This paper analyzed the characteristics of several types of active steering devices commonly used, and put forward a novel active steering device suitable for the bogies with the rocker type journal box positioning, which integrated two plunger cylinders in the rubber joint. When the train ran on a curve, such an active steering device could exert control over the plunger on one side to push the journal box to move in the longitudinal direction and relative to the frame, thus realizing the wheelset active steering. Finally, the proposed active steering device was proven with excellent performance according to the analysis results. The research results provide a technical idea for the engineering application of the wheelset active steering technology.